The Yin and Yang of Targeting KLRG1+ Tregs and Effector Cells - Borys, Samantha M.; Bag, Arup K.; Brossay, Laurent; Adeegbe, Dennis O. (Frontiers in Immunology, 2022)
The literature surrounding KLRG1 has primarily focused on NK and CD8+ T cells. However, there is evidence that the most suppressive Tregs express KLRG1. Until now, the role of KLRG1 on Tregs has been mostly overlooked and remains to be elucidated. Here we review the current literature on KLRG1 with an emphasis on the KLRG1+ Treg subset role during cancer development and autoimmunity. KLRG1 has been recently proposed as a new checkpoint inhibitor target, but these studies focused on the effects of KLRG1 blockade on effector cells. We propose that when designing anti-tumor therapies targeting KLRG1, the effects on both effector cells and Tregs will have to be considered.